Pressure and interaction measure of the gluon plasma - Antonov, Dmitry; Pirner, Hans J.; Schmidt, Michael G. (Nuclear physics. A, Nuclear and hadronic physics, 2010)
We explore the thermodynamics of the gluon plasma in SU(3) Yang-Mills theory emerging from the nontrivial spatial dynamics of valence gluons. The lattice data suggest that these gluons interact with each other linearly at large spatial separations. At high temperatures, valence gluons should reproduce the pressure of the noninteracting Stefan-Boltzmann plasma along with the leading perturbative correction. These properties of valence gluons can be modeled in terms of the integral over their trajectories. We calculate such a world-line integral analytically and obtain the pressure and the interaction measure (ε−3p)/T4 of the gluon plasma. Additionally, we account for the contributions of stochastic background fields to these thermodynamic quantities. The results turn out to be in a good agreement with the corresponding lattice data. In particular, the lattice-simulated peak of the interaction measure near the deconfinement critical temperature is reproduced.